Isolation and biological characterization of the broad host range bacteriophage ΨSA118 for the biocontrol of Staphylococcus aureus in food safety applications - Hong Phuoc, Man; Dinh Duy, Nguyen; Thi Hoa, Nguyen; Thu, Ha Thi; Hien, Vu Thi; Lanh, Pham Thi; Quyen, Dong Van (Academia Journal of Biology, 2026)
Staphylococcus aureus is a significant foodborne pathogen responsible for numerous outbreaks of food poisoning worldwide. Its increasing resistance to commonly used antibiotics, including methicillin, poses a critical challenge to food safety and public health, necessitating the development of alternative antimicrobial strategies. Bacteriophages (phages), as natural bacterial predators, offer a promising biocontrol approach due to their host specificity and ability to self-amplify at the site of infection. In this study, 25 bacteriophage isolates were screened for lytic activity against S. aureus, among which phage ΨSa118 was identified as the most promising candidate. Phage ΨSa118 exhibited a broad intraspecies host range, lysing all 9 tested S. aureus strains, while demonstrating strict species specificity. Transmission electron microscopy (TEM) revealed that ΨSa118 possesses an icosahedral head with a very short and non-contractile tail, classifying it within the Podoviridae family. Biological characterization showed that ΨSa118 achieved optimal replication at a multiplicity of infection (MOI) of 0.01, reaching a peak titer of 3.50 × 109 PFU/mL. The phage had a latent period of 20 minutes and a burst size of 73 PFU per infected cell, indicating efficient lytic potential. Environmental stability assays demonstrated that ΨSa118 remained viable across a wide range of conditions, including temperatures from 4 oC to 50 oC, pH levels from 2 to 12, and NaCl concentrations up to 10 M. Additionally, ΨSa118 maintained its viability following prolonged exposure to UV radiation (254 nm), further supporting its resilience. Taken together, these findings indicate phage ΨSa118 as a potent biocontrol agent against S. aureus, especially where conventional antimicrobials are limited by resistance or regulation.